Students’ Reading Comprehension in Descriptive Text - Walidah Sofyan Siregar; Eka Sustri Harida (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research is discussing about the students’ reading comprehension of the second year MTs.Muhammadiyah 22 Padangsidimpuan. This research employed descriptive quantitative research. Based on the result of the research, researcher got the description of the data was found that mean score was 56.76. It means that the students’ reading comprehension of the second year MTs.Muhammadiyah 22 Padangsidimpuan was categorized into enough ability. Then, from the result of the hypothesis testing, the researcher found that Zcount =-3.57Ztable 0.3264. It means the hypothesis was rejected. Thus, the result of mean scores the students’ ability in enough ability and actually it should be accepted hypothesis, but based on the result of that score it is rejected. So, maybe there is a mistake in instrument or in calculation.